A population‐based case–control study of the association between weather‐related extreme heat events and orofacial clefts. Issue 19 (19th October 2018) - Soim, Aida; Sheridan, Scott C.; Hwang, Syni‐An; Hsu, Wan‐Hsiang; Fisher, Sarah C.; Shaw, Gary M.; Feldkamp, Marcia L.; Romitti, Paul A.; Reefhuis, Jennita; Langlois, Peter H.; Browne, Marilyn L.; Lin, Shao; et al.
Abstract : Background: Limited epidemiologic research exists on the association between weather‐related extreme heat events (EHEs) and orofacial clefts (OFCs). We estimated the associations between maternal exposure to EHEs in the summer season and OFCs in offspring and investigated the potential modifying effect of body mass index on these associations. Methods: We conducted a population‐based case–control study among mothers who participated in the National Birth Defects Prevention Study for whom at least 1 day of their first two post‐conception months occurred during summer. Cases were live‐born infants, stillbirths, and induced terminations with OFCs; controls were live‐born infants without major birth defects. We defined EHEs using the 95th and the 90th percentiles of the daily maximum universal apparent temperature distribution. We used unconditional logistic regression with Firth's penalized likelihood method to estimate adjusted odds ratios and 95% confidence intervals, controlling for maternal sociodemographic and anthropometric variables. Results: We observed no association between maternal exposure to EHEs and OFCs overall, although prolonged duration of EHEs may increase the risk of OFCs in some study sites located in the Southeast climate region. Analyses by subtypes of OFCs revealed no associations with EHEs. Modifying effect by BMI was not observed. Conclusions: We did not find a significantly increased risk of OFCs associated with maternal exposure to EHEs during the relevant window of embryogenesis. Future studies should account for maternal indoor and outdoor activities and for characteristics such as hydration and use of air conditioning that could modify the effect of EHEs on pregnant women.